The Evidence of Cadmium (Cd) Heavy Metal in South Asian Apple snail (Pila ampullacea) on The Batu Kuta Village Narmada District - Widya Septiani; Khairuddin Khairuddin; M. Yamin (Jurnal Biologi Tropis, 2022)
Waste produced by society has a negative impact on the environment such as waste from agricultural, household, and industrial sector. The study aims to evaluate the content of heavy metal Cadmium (Cd) in rice field snail (Pila ampullacea) as a pollutant indicator in Narmada sub-district, West Lombok. The research method used observation and laboratory. Furthermore, Sampling at six points was conducted with three repetitions. In addition, the heavy metal content of the research sample was analyzed using AAS (Atomic Absorption Spectrophotometry). The result indicated that the average of heavy metal content Cadmium (Cd) per point in rice field snail (Pila ampullacea) in Batu Kuta village, Narmada sub-district ranged from 0.367 ppm – 0.554 ppm. The highest value was found in the rice field at station 2 point 3, while the lowest was in the irrigation canal at station 2 point 1. The average of the analysis on the heavy metal content Cadmium (Cd) per station in rice field snail (Pila ampullacea) with the highest value of 0.481 ppm was found at station 1, while the lowest value of 0.465 ppm was at station 2. It can be concluded that the heavy metal content of Cadmium in snail is an indicator that society activities, especially in agricultural sector, have a negative impact on the environment. Hence, the result of the study is able to be a source of scientific information for environmentally friendly agricultural system management policies, especially in the study site and other location.